2021
DOI: 10.3389/fchem.2021.644691
|View full text |Cite
|
Sign up to set email alerts
|

Practical and Computational Studies of Bivalence Metal Complexes of Sulfaclozine and Biological Studies

Abstract: In the search for novel, metal-based drug complexes that may be of value as anticancer agents, five new transition metal complexes of sulfaclozine (SCZ) with Cu(II), Co(II), Ni(II), Zn(II), and Fe(II) were successfully synthesized. The chemical structure of each complex was characterized using elemental analysis (CHN), IR spectroscopy, UV–Vis spectroscopy, thermogravimetric analysis (TGA), and electronic paramagnetic resonance (EPR) spectroscopy. IR spectra indicated that the donor atoms were one sulfonyl oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 71 publications
1
17
0
Order By: Relevance
“…Molecular docking helps us to understand the possible modes of interaction and binding affinities of new compounds as targeted drug molecules, which may offer better insight into how well they exert bioactivity against the target [45]. The docked complex conformations were evaluated according to the docking scores and binding interactions of the ligands and oxidovanadium(IV) complexes with the hepatocellular carcinoma (ID: 1JU6) and breast cancer (ID: 1HK7) proteins, which were selected according to the literature and previous studies [49]. The docking study results indicated that the ligands and synthesized complexes involve non-covalent interactions, such as π-cation, π-π, ionic, and hydrogen bonding interactions, as presented in Table S7.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Molecular docking helps us to understand the possible modes of interaction and binding affinities of new compounds as targeted drug molecules, which may offer better insight into how well they exert bioactivity against the target [45]. The docked complex conformations were evaluated according to the docking scores and binding interactions of the ligands and oxidovanadium(IV) complexes with the hepatocellular carcinoma (ID: 1JU6) and breast cancer (ID: 1HK7) proteins, which were selected according to the literature and previous studies [49]. The docking study results indicated that the ligands and synthesized complexes involve non-covalent interactions, such as π-cation, π-π, ionic, and hydrogen bonding interactions, as presented in Table S7.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…KSV can be obtained from the slope of the plot of F o /F vs . [DNA] or the concentration of the tested drug [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Frontier molecular orbitals, Highest occupied molecular orbital (HOMO) and Lowest unoccupied molecular orbital (LUMO) properties depict the electrons in a stable compound. [ 45 ] HOMO and LUMO is assuming a significant part in the study of chemical reactivity and optical properties. HOMO and LUMO energies of the synthesized compounds in the ground state were calculated and are presented in Figure 9a,b.…”
Section: In Silico Admet Studiesmentioning
confidence: 99%